The madness of crowds [compact disc, unabridged] : a novel - Penny, Louise (Macmillan Audio, 2021)
When a visiting professor spreads lies so that fact and fiction are so confused it's nearly impossible to tell them apart, leading to murder, Chief Inspector Armand Gamache must investigate this case as well as this extraordinary popular delusion.